An Explanatory Study of User Motivations for Participating in Online Collaborative Consumption - Alsaedi, Reem (2017)
Information and communication technologies have boosted a new culture of consumption so-called peer-to-peer Online Collaborative Consumption (OCC). Although it is expected that OCC may bring many benefits to society such as alleviating mass consumption, pollution, and poverty, there is a limited understanding beyond anecdotal evidences as to why users participate in OCC activities based on research, particularly in Saudi Arabia. The sustained success of peer-to-peer OCC is mainly based on understanding the behaviour of potential providers who own and supply resources and the customers who need these resources. The term “online collaborative consumption” is often vague and is used interchangeably with other sharing economy concepts. The forces driving the emergence of OCC and its barriers to success are not clearly defined. Therefore, this research develops a clear definition of OCC, identifies the driving forces and barriers for OCC marketplaces, and investigates user motivations for participating in OCC. These objectives are achieved through studying relevant literature, and employing survey data collected from 106 registered users of the Saudi OCC platform. The findings demonstrate that participation in OCC activities is influenced by several factors such as trust, economic benefits, and environmental benefits. An interesting result is that trust had the strongest positive effect on participation in OCC. Furthermore, trust is not directly related with actual participation unless concurrently it is positively related with attitude towards OCC. This suggests that the trust as motivation could only be important when users have trust beliefs toward OCC platforms. Thus, the importance of establishing adequate trust mechanisms such as word-of-mouth (rating and reviews systems) in OCC platforms is recommended to build trust and security beliefs among users. Additionally, the results show that a discrepancy between user attitudes and behaviours in OCC might occur; positive attitudes towards OCC might be not necessarily translate into actual behaviour.